Outcomes and clinical features associated with surgically excised canine salivary gland carcinoma: A multi‐institutional, retrospective, Veterinary Society of Surgical Oncology study. Issue 3 (16th January 2023) - Bush, Kaleigh M.; Grimes, Janet A.; Linden, Daniel S.; Plavec, Tanja; Kessler, Martin; Rossanese, Matteo; Bennett, Barbara; Chadsey, Laura; Coggeshall, Whitney S.; Matz, Brad M.
Abstract: Objective: The objective of this study was to describe the clinical features, prognostic factors, and outcomes in dogs with surgically treated salivary gland carcinoma. Study design: Multi‐institutional retrospective case series. Animals: Seventy‐two client‐owned dogs from 16 institutions with surgically excised salivary gland carcinoma. Methods: Medical records of dogs undergoing sialoadenectomy from January 1, 2000 to January 1, 2020 were reviewed for signalment, clinical signs, preoperative staging results, preoperative mass evaluation, complications, histopathologic diagnosis, local recurrence, metastatic disease, and survival times. Survival functions were estimated using the Kaplan‐Meier estimator. Factors related to survival were individually tested using the log‐rank test. Results: The overall median survival time (MST) associated with salivary carcinoma was 1886 days. Local recurrence occurred in 29/69 (42%) dogs with an overall disease‐free interval (DFI) of 191 days. Metastatic disease occurred in 22/69 (31.9%) dogs, with an overall DFI of 299 days. Lymph node metastasis was present at the time of surgery in 11/38 (28.9%) dogs in which lymphadenectomy was performed at the time of surgery; these dogs had a shorter DFI at 98 days ( P  = .03) and MST at 248 days ( P  < .001). Conclusion: The prognosis for dogs with salivary gland carcinoma treated surgically was more favorable than previously reported. Nodal metastasis was a negative prognostic factor for canine salivary gland carcinoma. Clinical significance: Surgical intervention should be considered for dogs with salivary carcinoma.